2015
DOI: 10.1152/ajprenal.00609.2014
|View full text |Cite
|
Sign up to set email alerts
|

An angiotensin-(1–7) peptidase in the kidney cortex, proximal tubules, and human HK-2 epithelial cells that is distinct from insulin-degrading enzyme

Abstract: Angiotensin 1-7 [ANG-(1-7)] is expressed within the kidney and exhibits renoprotective actions that antagonize the inflammatory, fibrotic, and pro-oxidant effects of ANG II. We previously identified an peptidase that preferentially metabolized ANG-(1-7) to ANG-(1-4) in the brain medulla and cerebrospinal fluid (CSF) of sheep (Marshall AC, Pirro NT, Rose JC, Diz DI, Chappell MC. J Neurochem 130: 313-323, 2014); thus the present study established the expression of the peptidase in the kidney. Utilizing a sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 34 publications
1
32
0
Order By: Relevance
“…This peptide can be generated by either decarboxylation of the Asp residue of angiotensin- (1)(2)(3)(4)(5)(6)(7) or by catalytic action of angiotensin-converting enzyme-2 on decarboxylated AngII (also called angiotensin A) (Lautner et al, 2013). Two primary journal articles on alamandine, since its discovery, have paired this ligand with Masrelated G-protein-coupled receptor D; however, neither strong pharmacological nor direct radioligand binding data exist (Habiyakare et al, 2014;Wilson et al, 2015). Identification of alamandine and its putative receptor has attracted attention as a novel mediator of physiologic and pathophysiological actions of the RAS and may help to develop new therapeutic strategies for treating human cardiovascular diseases.…”
Section: A Pairing Mas Receptor With Ang (1-7)mentioning
confidence: 99%
“…This peptide can be generated by either decarboxylation of the Asp residue of angiotensin- (1)(2)(3)(4)(5)(6)(7) or by catalytic action of angiotensin-converting enzyme-2 on decarboxylated AngII (also called angiotensin A) (Lautner et al, 2013). Two primary journal articles on alamandine, since its discovery, have paired this ligand with Masrelated G-protein-coupled receptor D; however, neither strong pharmacological nor direct radioligand binding data exist (Habiyakare et al, 2014;Wilson et al, 2015). Identification of alamandine and its putative receptor has attracted attention as a novel mediator of physiologic and pathophysiological actions of the RAS and may help to develop new therapeutic strategies for treating human cardiovascular diseases.…”
Section: A Pairing Mas Receptor With Ang (1-7)mentioning
confidence: 99%
“…In contrast, peptidase activities derived by different synthetic substrates are not directly comparable unless standardized to enzyme content. Moreover, use of endogenous peptides may reveal novel peptidase activities involved in angiotensin processing (62,144). Peptidase assays developed in the author's laboratory use 125 I-radiolabled peptides coupled to HPLC-based separation and in-line ␥-detection (129).…”
Section: Ras Protein Componentsmentioning
confidence: 99%
“…Moreover, this activity was inversely correlated to CSF levels of Ang-(1-7) in control and betamethasone-exposed sheep, a model of fetal programming that exhibits elevated blood pressure and an attenuated baroreflex [7]. Subsequent studies found the Ang-(1-7)-degrading activity in sheep brain and kidney cortex, as well as in the human proximal tubule HK-2 cell line [57,98]. The enzyme activity exhibited unusual characteristics as Ang I and other peptides equal to or greater than 10 residues were not substrates for the peptidase [57,98].…”
Section: Dipeptidyl Peptidasementioning
confidence: 97%
“…Subsequent studies found the Ang-(1-7)-degrading activity in sheep brain and kidney cortex, as well as in the human proximal tubule HK-2 cell line [57,98]. The enzyme activity exhibited unusual characteristics as Ang I and other peptides equal to or greater than 10 residues were not substrates for the peptidase [57,98]. In addition, the peptidase was sensitive to both chelating agents such as o-phenanthroline and EDTA, and the sulfhydryl inhibitors APMA and PCMB [57,98].…”
Section: Dipeptidyl Peptidasementioning
confidence: 98%
See 1 more Smart Citation